Operation Shakespeare : the true story of an elite international sting - Shiffman, John. (Simon & Schuster, 2014)
"A Pulitzer Prize finalist presents the rare and intimate narrative of a daring national security sting designed to protect US soldiers, sailors, and pilots from the greatest danger they face on the battlefield--an enemy equipped with American-made weapons and technology. In Operation Shakespeare, investigative journalist John Shiffman traces an audacious and high-risk undercover operation--from Philadelphia to Shiraz to London to Beverly Hills to Tbilisi and Dubai. The sting is launched by an elite undercover Homeland Security unit created to stop the Iranians, Russians, Chinese, Pakistanis, and North Koreans from acquiring sophisticated American-made electronics capable of guiding missiles, jamming radar, and triggering countless weapons--from wireless IEDs to nuclear bombs. The US agents must outwit not only enemy brokers, but American manufacturers and global bankers too willing to put profit over national security. The three-year sting in Operation Shakespeare climaxes when the US agents lure the Iranian broker to a former Soviet republic with the promise of American-made radar, fighter-jet and missile components, then secretly drag him back to the United States, where he is held in secret for two years. The laptop the Iranian carries into the sting provides the CIA with a treasure trove, a virtual roadmap to Tehran's clandestine effort to obtain US military technology. Tenacious, richly detailed, broad in scope, and emotionally powerful--and boasting unprecedented access to the government agents fighting this shadow war, as well as the captured Iranian arms broker--Operation Shakespeare is a fast-paced and masterful account of the covert effort to preserve American military supremacy, and to protect US troops"--